The Effect of Payroll Accounting Information Systems on Improving the Effectiveness of Internal Control of Employee Salary Payments - Hermawan, Haslisa; Cahyana, Agus; Azis, Azolla Degita; Ningrum, N.ARumiasih. (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
This study discusses the effect of accounting information systems on internal control at PT Perfect Circle Engineering. With the aim of knowing how the payroll accounting information system is used and how internal control of employee salary payments is affected by it. This research uses a quantitative descriptive approach, primary data collection using observation methods and distributing questionnaires. The population in this study were all employees of PT Perfect Circle Engineering as many as 45 people, and as many as 30 people became samples in this study, all of which were returned to researchers. This study uses data quality test analysis, simple linear regression analysis, hypothesis testing and uses the IBM SPSS Statistics Version 23 program. The results of the author's research indicate that the implementation of the payroll accounting information system has been carried out properly in accordance with the procedure. and the system that has been used has a significant effect on how effective internal control of employee salary payments is.